Report on industrial atttachment with Shell Eastern Petroleum (Pte) Ltd - Fajar Firdaus Abdi (2008)
Author developed software for remnant life assessment of high-alloyed steel furnace tubes for hydrogen, ethylene, and direct iron reduction synthesis gas manufacturing.